Effect of the crosslinking agent on the biorepulsive and mechanical properties of polyglycerol membranes - Balser, Sebastian; Zhao, Zhiyong; Zharnikov, Michael; Terfort, Andreas (Colloids and surfaces. B, Biointerfaces, 2023)
Polyglycerol (PG) based surfaces materials and surfaces are well-established bio-compatible materials. Crosslinking of the dendrimeric molecules via their OH groups improves their mechanical stability up to the point that free-standing materials can be attained. Here, we investigate the effect of different crosslinkers on PG films regarding their biorepulsivity and mechanical properties. For this purpose, PG films with different thicknesses (15, 50 and 100 nm) were prepared by polymerizing glycidol in a ring-opening polymerization onto hydroxyl-terminated Si substrates. These films were then crosslinked using ethylene glycol diglycidyl ether (EGDGE), divinyl sulfone (DVS), glutaraldehyde (GA), 1,11-di(mesyloxy)−3,6,9-trioxaundecane (TEG-Ms2) or 1,11-dibromo-3,6,9-trioxaundecane (TEG-Br2), respectively. While DVS, TEG-Ms2, and TEG-Br2 resulted in slightly thinned films, presumably due to loss of unbound material, increase of film thickness was observed with GA and, in particular, EDGDE, what can be explained by the different crosslinking mechanisms. The biorepulsive properties of the crosslinked PG films were characterized by water contact angle (WCA) goniometry and various adsorption assays involving proteins (serum albumine, fibrinogen, γ-globulin) and bacteria (E. coli), showing that some crosslinkers (EGDGE, DVS) improved the biorepulsive properties, while others deteriorated them (TEG-Ms2, TEG-Br2, GA). As the crosslinking stabilized the films, it was possible to use a lift-off procedure to obtain free-standing membranes if the thickness of the films was 50 nm or larger. Their mechanical properties were examined with a bulge test showing high elasticities, with the Young’s moduli increasing in the order GA ≈ EDGDE < TEG-Br2 ≈ TEG-Ms2 < DVS.
Gesehen am 17.08.2023